A comparative study of three different doses of nalbuphine as an adjuvant to intrathecal bupivacaine for postoperative analgesia in abdominal hysterectomy - Fareed Ahmed (Indian Journal of Pain, 2016)
Background: Spinal anesthesia is still the most commonly used technique for lower abdominal surgeries as it is very economical and easy to administer. Its main disadvantage remains the short duration of action. Hence, different additives have been used. Nalbuphine is an agonist-antagonist opioid that binds to μ-receptors, as well as to κ-and δ-receptors. The aim of this randomized, double-blind study was to evaluate the potentiating effect of intrathecal nalbuphine with bupivacaine for postoperative analgesia in three different doses. Materials and Methods: A total of 100 patients were randomized into four groups. Group A: Patients received 15 mg of 0.5% hyperbaric bupivacaine, group B: Patients received 15 mg of 0.5% hyperbaric bupivacaine plus 0.8 mg of nalbuphine, group C: Patients received 15 mg of hyperbaric bupivacaine plus 1.6 mg of nalbuphine, and group D: Patient received 15 mg of hyperbaric bupivacaine plus 2.4 mg of nalbuphine intrathecally. Results: The onset of sensory and motor block and duration of motor block were comparable in all groups. Two-segment regression was statistically significant when group A was compared to groups B, C, and D. The total durations of analgesia were 133.8 + 28.3 min, 199.8 + 25.9 min, and 166.8 + 27.8 min in groups B, C, and D, respectively. Conclusion: Our study showed that the combination of intrathecal bupivacaine with nalbuphine significantly prolonged postoperative analgesia as compared to the control group, and a 1.6 mg dose of nalbuphine administered intrathecally showed the best results among all other study groups.